2017
DOI: 10.3390/ijms18091797
|View full text |Cite
|
Sign up to set email alerts
|

Human CD3+ T-Cells with the Anti-ERBB2 Chimeric Antigen Receptor Exhibit Efficient Targeting and Induce Apoptosis in ERBB2 Overexpressing Breast Cancer Cells

Abstract: Breast cancer is a common malignancy among women. The innate and adaptive immune responses failed to be activated owing to immune modulation in the tumour microenvironment. Decades of scientific study links the overexpression of human epidermal growth factor receptor 2 (ERBB2) antigen with aggressive tumours. The Chimeric Antigen Receptor (CAR) coding for specific tumour-associated antigens could initiate intrinsic T-cell signalling, inducing T-cell activation, and cytotoxic activity without the need for major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…After incubation at 32°C, the supernatant was collected and filtered through a 0.45 μm pore size membrane filter (Millipore, Burlington, Massachusetts, USA). 8 μg of HDMB (Sigma-Aldrich Química S.A.) was added per ml of retroviral supernatants [28,46], and this mixture was employed for the infection of MSCs at 70% confluence in 6-well adherent culture dishes (Costar Corning Incorporated) ( Figure 1). No viruses were added to one well of each dish, which was used as a negative control for antibiotic selection.…”
Section: Msc Spinoculation With Retrovirus Produced By Phoenixmentioning
confidence: 99%
See 2 more Smart Citations
“…After incubation at 32°C, the supernatant was collected and filtered through a 0.45 μm pore size membrane filter (Millipore, Burlington, Massachusetts, USA). 8 μg of HDMB (Sigma-Aldrich Química S.A.) was added per ml of retroviral supernatants [28,46], and this mixture was employed for the infection of MSCs at 70% confluence in 6-well adherent culture dishes (Costar Corning Incorporated) ( Figure 1). No viruses were added to one well of each dish, which was used as a negative control for antibiotic selection.…”
Section: Msc Spinoculation With Retrovirus Produced By Phoenixmentioning
confidence: 99%
“…Therefore, strategies to enhance infection efficiency should be employed. One of these strategies is spinoculation, which has been used during decades to improve viral infection of several types of cells in vitro [21][22][23][24][25][26][27][28][29][30][31][32][33][34] (Table 1), although the process responsible for spinoculation-induced enhancement of infection has not been discovered yet [33]. However, it is known that the enhancement of infection induced by spinoculation is cell type-dependent [20,25] and also related to the speed of centrifugation [33] in a cell type-dependent manner [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies suggested that HRG1β-based CAR-T cells successfully inhibit breast cancer proliferation through HER family receptors and able to deliver an attractive therapeutic approach to defeat cancer resistance against HER2-based targeted therapy [62]. In parallel, Munisvaradass et al found that human anti-HER2 CAR T cells showed desirable targeting and triggered cell death in HER2 overexpressing breast cancer cells [63]. Moreover, mesothelin recognition by special CAR T cells has been described as a promising immunotherapy goal for breast cancer treatment [64].…”
Section: Breast Cancermentioning
confidence: 99%
“…The scFv redirects CAR-T cells to recognize cancer cells in an HLA (human leukocyte antigen)-independent manner and the TCR intracellular domain induces T-cell dependent cancer killing [14,15] . After the remarkable demonstration of efficiency by the first engineered T cells pioneered by Eshhar and coworkers [16] , variability in T cell functionalities have emerged.…”
Section: Introductionmentioning
confidence: 99%